PENGARUH RASIO KEMANDIRIAN DAERAH, EFEKTIFITAS PENDAPATAN ASLI DAERAH, DAN PENGELOLAAN BELANJA DAERAH TERHADAP KINERJA KEUANGAN DAERAH - RAUHUL IJTIHAD; IWAN HARSONO (GANEC SWARA, 2024)
This study aims to test and analyze the effect of independence, effectiveness of local original income and regional expenditure on regional financial performance at the Regional Finance and Asset Management Agency of West Nusa Tenggara Province (RFAMA). This research is quantity with the type of data in the form of documentary data. The population used in this study is all regencies and cities in East Java Province consisting of 2 cities and 8 regencies contained in the Regional Finance and Asset Management Agency of West Nusa Tenggara Province (RFAMA) with an observation period in 2011-2021. The sampling technique in this study is a purposive sampling technique with a sample number of 110 data. The study was analyzed by simple linear regression using the SPSS program. The results of this study show that Regional Independence and Regional Revenue Effectiveness do not affect Regional Financial Performance, on the contrary, Regional Expenditure has a positive effect on Regional Financial Performance.